Guidance on Islamic Counseling from the Perspective of the Al-Qur'an Surah Al-Imran Verses 159-160 - Dina Furqoni Fauzi (al-Afkar, Journal For Islamic Studies, 2025)
Islamic counseling guidance has the goal of helping individuals to solve the problems they are facing through the approach of the Qur'an or Hadith. This research focuses on finding the values ​​of Islamic guidance and counseling contained in Surah Al Imran verses 159-160. This research is a type of library research (library research), namely research that focuses discussion on the literature in the form of books, journals, papers, and other writings. Which is done by reading books related to Islamic guidance and counseling. Data collection techniques use documentation of book studies. The data analysis technique is to examine objects that are qualitative in nature using the Maudhu'i method. This discussion resulted in the existence of Islamic counseling guidance values ​​in Surah Al Imran verses 159-160, including: Gentle, forgiving, deliberative and trustful, where these values ​​need to be applied during the counseling process.